Back Cover: Oxidative Metalation as a Route to Size‐Mismatched Macrocyclic Complexes: Osmium Corroles (Angew. Chem. Int. Ed. 52/2014). Issue 52 (4th December 2014) - Alemayehu, Abraham B.; Gagnon, Kevin J.; Terner, James; Ghosh, Abhik
<x xml:space="preserve">Abstract</x> Heavy‐element corroles are of great interest as optical sensors, near‐IR dyes, phosphors, organic light‐emitting diodes, and anticancer compounds, but the insertion of 5d metals into corroles is difficult. In their Communication on page 14411 ff., A. Ghosh and co‐workers present the oxidative metalation of meso triarylcorroles with [Os3(CO)12]/NaN3 as a route to nitridoosmium(VI) corroles. These complexes exhibit distinctive domed folded macrocycles and multiple Os–nitrido stretching frequencies.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>